Atypical neurological manifestations in anti-IgLON5 disease: a case report - Chen, Yun; Chen, Jingyao; Pei, Zhaohua; Qian, Wei (Frontiers in Neurology, 2024)
Anti-IgLON5 disease is a recently discovered autoimmune encephalopathy with sleep disorder as a hallmark in the majority of reported cases. Additional neurological manifestations include bulbar dysfunction, gait problems, movement disorders, oculomotor abnormalities, and hyperexcitability of the nervous system. At present, an increasing number of publications have dealt with the course and possible treatment options for anti-IgLON5 disease, and its clinical spectrum has expanded wider and more heterogeneous. Here, we report a case of a 66-year-old female with cognitive impairment accompanied by slow reaction, impaired memory, and decreased orientation. A positive cerebral MRI change and serum and cerebrospinal fluid (CSF) antibodies against IgLON5 were found during the diagnostic course. Subsequently the patient received immunotherapy and was generally in good health with no new symptoms during follow-up. Early testing for IgLON5 antibodies should be considered in patients with atypical neurological symptoms such as cognitive impairment, slow reaction, or decreased orientation. In clinical practice, immunotherapy should be considered in all cases of anti-IgLON5 encephalopathies.